Evaluating the effects of medium chain fatty acids on nursery pig health and performance compared to traditional feed supplements carbadox and zinc oxide - Koetting, Aleesha R.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Carbadox and Zinc Oxide (ZnO) are traditional supplements for nursery pig diets, but have many modern disadvantages, including negative environmental impacts. By testing different medium chain fatty acid (MCFA) supplements for nursery diets, performance aspects including ADG, ADFI, and G:F were investigated. The 35-day study follows 360 weanling pigs (DNA 200x400: 5.4+/-0.07 kg) being fed one of 6 dietary treatments. Pigs were randomly assigned to 10 pens per treatment with 6 pigs per pen. The 6 dietary treatments included: 1) control; 2) 3,000 ppm ZnO in Phase 1 and 1,500 ppm ZnO in Phase 2; 3) 50 g/ton carbadox; 4) 1% blend of C6:C8:C10; 5) 1% Feed Energy R2 (Feed Energy Corp, Des Moines, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Diets were split into 3 phases, with treatment diets in Phase 1 (d0 to d7) and Phase 2 (d8 to d19), while Phase 3 (d20 to d35) was a common diet. Piglet weights and feeder weights were collected weekly. Piglets fed ZnO or carbadox had greater (P<0.05) ADG and ADFI compared to the control, with pigs fed FORMI being intermediate. Pigs fed C6:C8:C10 and R2 had decreased (P<0.05) ADFI, possibly due to a taste or palatability issue, which likely caused a related decrease (P<0.05) in ADG. Under the conditions of this experiment it was found that pigs fed traditional feed supplements ZnO and carbadox had the greater performance compared to the control, while those fed MCFA had varied outcomes. In conclusion, further studies are needed to evaluate if MCFAs are an adequate replacement for ZnO and carbadox.
Keywords: Spring 2019